Retention and future involvement in the American Kennel Club Junior Showmanship Program, a youth dog breed conformation competition - Loonsk, Hannah L.; Clarke, Dana L.; Battaglia, Carmen; Otto, Cynthia M. (Frontiers in Veterinary Science, 2022)
Similar to other organizations that encourage positive youth development, the American Kennel Club (AKC) created the Junior Showmanship program to develop skills and pave a path for the next generation of competitors in canine conformation. Although participants age out of the Junior Showmanship Program when they turn eighteen, the hope is that Juniors will continue to be active in dog sports into adulthood. Females are overly represented in all age groups in this survey and in current participation. Although both males and females most commonly stopped participating at age 17 or 18, males had a significantly higher drop out at age 15. Further study is warranted to investigate factors specifically pertaining to male participation. A strong Belief System Model which accounted for positive responses associated with camaraderie and mentoring during the showmanship program was significantly (p=0.01) associated with commitment, member interest and active participation as an adult. In addition, success in the show ring was associated with future involvement in conformation or dog sports. Thus, both perceived achievement and mentorship by adult “volunteers” were associated with continued participation.